Application value of multi-gene mutation detection in the clinical management of pediatric papillary thyroid carcinoma: a preliminary exploration - Wang, Yuguo; Wang, Hui; Tan, Gongxun; Wu, Xinping; Wang, Bin; Tan, Zhihan; Du, Jing; Li, Xiuying; Xu, Ying; Yan, Na; Qian, Xiaoqin (Frontiers in Endocrinology, 2024)
Objectives: Thyroid cancer rarely occurs in children and adolescents. Molecular markers such as BRAF, RAS, and RET/PTC have been widely used in adult PTC. It is currently unclear whether these molecular markers have equivalent potential for application in pediatric patients. This study aims to explore the potential utility of a multi-gene conjoint analysis based on next-generation targeted sequencing for pediatric papillary thyroid carcinoma (PTC). Materials and methods: The patients diagnosed with PTC (aged 18 years or younger) in the pediatrics department of Lishui District Hospital of Traditional Chinese Medicine were retrospectively screened. A targeted enrichment and sequencing analysis of 116 genes associated with thyroid cancer was performed on paraffin-embedded tumor tissues and paired paracancerous tissue of fifteen children (average age 14.60) and nine adults (average age 49.33) PTC patients. Demographic information, clinical indicators, ultrasonic imaging information and pathological data were collected. The Kendall correlation test was used to establish a correlation between molecular variations and clinical characteristics in pediatric patients. Results: A sample of 15 pediatric PTCs revealed a detection rate of 73.33% (11/15) for driver gene mutations BRAF V600E and RET fusion. Compared to adult PTCs, the genetic mutation landscape of pediatric PTCs was more complex. Six mutant genes overlap between the two groups, and an additional seventeen unique mutant genes were identified only in pediatric PTCs. There was only one unique mutant gene in adult PTCs. The tumor diameter of pediatric PTCs tended to be less than 4cm (p<0.001), and the number of lymph node metastases was more than five (p<0.001). Mutations in specific genes unique to pediatric PTCs may contribute to the onset and progression of the disease by adversely affecting hormone synthesis, secretion, and action mechanisms, as well as the functioning of thyroid hormone signaling pathways. But, additional experiments are required to validate this hypothesis. Conclusion: BRAF V600E mutation and RET fusion are involved in the occurrence and development of adolescent PTC. For pediatric thyroid nodules that cannot be determined as benign or malignant by fine needle aspiration biopsy, multiple gene combination testing can provide a reference for personalized diagnosis and treatment by clinical physicians.